Metodologi Penafsiran Muhammad Shahrur dalam Memahami Teks (Analisis Kritis terhadap Relevansi Aplikatif Teori Limits) - R. Zainul Mushthofa (Proceedings of Annual Conference for Muslim Scholars, 2017)
Changing times is an unavoidable necessity along with the progress of civilization of a nation. Along with the change in the law was also progressing to adjust to the circumstances of the times. In this regard, Shahrur offers a concept in the call with the "theory of limits". It is therefore important to question how the issues surrounding the background of the theory of limits. What methods are used Shahrur in understanding the text and what the advantages and disadvantages of the theory of limits. The emergence of this theory is due to the rigidity of thinking beings are characterized by dependency all legal matters to their priests. What was delivered by scholars earlier fixed it without trying to catch hold of reviewing whether his opinions are still relevant to current conditions. This is why Islamic law can not evolve as time advances. Therefore, Shahrur do penggugahan against thinking kemapan previous scholars by offering the concept of hudud (theoretical limit). For Shahrur the law should be shalih li kulli zaman wa makan. The law should be applied in every time and place.Keywords: Motodologi interpretation, Shahrur, Theory Limits